Leadership 4.0 and performance allowances: Their impact on the motivation of employees of the housing and settlement office of the Bandar Lampung City Government - Aulia Rossa Henita (Technium Social Sciences Journal, 2023)
This research study is about improving the performance of employees of the Bandar Lampung City Housing and Settlement Office through the influence of the implementation of Leadership 4.0 and performance allowances. The approach used in research is a quantitative approach based on numerical data obtained through efforts to provide questionnaires and literature studies, and data analysis efforts are carried out using measurement methods and structural methods. The results showed that leadership 4.0 had a significant positive effect on employee motivation at the Bandar Lampung City Government Housing and Settlement Office as seen from the leadership 4.0 value of 2,608 while the value was 1.96, and the signification value (sig.) of 0.009 < 0.05, meaning that leadership by current conditions can provide positive motivation for employees in maximizing their performance to realize organizational goals, while performance allowances show that performance allowances do not have a significant positive effect on employee motivation at the Bandar Lampung City Government Housing and Settlement Office, as seen from the value of performance allowances of 1,677 While the value is 1.96, and the signification value (SIG.) is 0.094 > 0.05. The absence of the effect of performance allowances shows that so far the benefits provided do not affect the work motivation of employees because it is caused by the inconsistency of distribution of performance allowances to employees in other words, benefits often experience delays even more than 6 months, performance allowances have only been paid to employees.